Correction: Singano et al. One Health Lens on Rabies: Human–Bat Interactions and Genomic Insights of Rabies Virus in Rural Lilongwe, Malawi. Trop. Med. Infect. Dis. 2025, 10, 95 - Singano, Nathan; Kainga, Henson; Chatanga, Elisha; Nkhoma, Joseph; Njunga, Gilson; Chulu, Julius; Tembo, Rabecca; Sawa, Hirofumi; Muleya, Walter (Tropical medicine and infectious disease, 2025)
There was an error in the original publication [...]